The Potential Economic Impacts of Cryptocurrency in Indonesia: A Systematic Literature Review - Eogenie Lakilaki; Windy Permata Suyono; Angger Hidayat; Nur Jumriantunnisah; Febri Pramudya Wardani (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
Cryptocurrency emergence poses significant challenges and opportunities for Indonesia's economy, yet comprehensive understanding of its economic impacts remains limited. This study employs a systematic literature review to analyze cryptocurrency's potential economic implications in Indonesia by examining stakeholder expectations, regulatory frameworks, and economic impacts. The research extracted and synthesized findings from ten studies using qualitative, empirical economic, and regulatory analysis methodologies. Results reveal a regulatory dichotomy between Bank Indonesia's stability-focused approach and the Ministry of Trade's growth-oriented perspective, creating market uncertainty. Cryptocurrency positively impacts banking stock prices, payment system efficiency, and investment opportunities, while raising concerns about volatility, monetary control, and cybersecurity. Stakeholder expectations vary across banking, fintech, regulatory, and investor groups, highlighting the need for balanced regulatory approaches that foster innovation while addressing systemic risks. This research contributes valuable insights for developing comprehensive cryptocurrency policies that maximize economic benefits while maintaining financial stability.